Dietary Risk Assessment Due to the Consumption of Polycyclic Aromatic Hydrocarbon in Two Commonly Consumed Street Vended Foods. (28th May 2022) - Ankar-Brewoo, Gloria Mathanda; Darko, Godfred; Abaidoo, Robert Clement; Dalsgaard, Anders; Johnson, Paa-Nii; Ellis, William Otoo; Brimer, Leon
Abstract: Polycyclic aromatic hydrocarbons (PAH) are present and pervasive in the environment. Handling of the foods by the vendors is therefore likely to introduce PAHs into the meals. Quantification of PAH was made using HPLC-FID and consumption data by face–face interviews with 188 regular consumers for the vendors. Data obtained were iterated 10, 000 times using palisade @risk software and results presented at 95th percentile level of consumption showing the worst case scenario. Dietary risk assessment of 12-priority PAHs was carried out on the components of two staple foods in Ghana. Naphthalene was detected in all food samples at concentrations ranging from 1.7 to 6.5 mg kg − 1 at 95th percentile consumption level. Benzo(a)pyrene and dibenz-a, h-anthracene were detected in fried chicken samples with the stochastic concentrations of 1.2E–02 mg kg − 1 and 3.2E–03 mg kg − 1, respectively, at the 95th percentile level of consumption. Incremental life cancer risk values fell within the deminis value of ≤10 − 6 to 10 − 4 except at the 95th percentile level of consumption of chicken, hot pepper sauce, and soup components of the meals which were higher (10 − 3 ). The 95th percentile level of consumption of fried rice meal as well as the 50th and 95th percentile level of consumption of the fufu meal had a hazard index above 1, indicating consumers may be suffering the non-carcinogenic effects due to PAH in the respective meals. The study, therefore, showed that high consumption levels of the street vended foods are likely to cause dietary risk to the health of its consumers.